The socio-demographic dimensions of health spending equity: An empirical analysis of municipalities in São Paulo State, Brazil - Alinsunurin, Jason P. (Animo Repository, 2019)
Developing countries across the world continue to face the pressure to deliver high-quality health services to its citizens. Public health systems have always been constrained to face the challenges of potentially sociodemographic shifts. Brazil is not an exception in this case. Its municipalities are responsible for implementing most health policies and the population structure is rapidly aging. In this paper, our aim is to explain the co-evolution of inequality of health expenditures at the sub-national level with the the socio-demographic shift. Theoretical Framework. Despite the constitutional guarantee of universal health coverage (UHC) in Brazil, there are persistent inequities in the burden of public health spending. Moreover, most health decentralization policies in Brazil are implemented at the local government levels. This potentially raises issues of economies of scale and size in terms of health service delivery. The dependence of the municipalities from federal fiscal transfers and how this relates to health expenditures inequities are yet to be explored empirically; more importantly, the demographic shift in Brazil towards an aging population structure will certainly influence resource flows, as well as private health spending among the population. Methods and initial results. We situate our study in the context of S˜ao Paulo State, Brazil, representing about 21 percent of the Brazilian population. We started by analyzing the profile of 645 municipalities from 2009 to 2016; reasonably extrapolating projections based on the census and published data sources. Our ongoing and initial econometric analyses show evidence that a changing demographic structure (particularly that of an aging population) raises health spending and transfers among municipalities (if the share of senior citizens in a municipality increases by 10 percent, the cost of health expenditures per inhabitant increases by 6.3 percent). We also have initial evidence showing federal fiscal transfers constitute the substantial health expenditures municipalities, possibly demonstrating fiscal sharing mechanisms between levels of government. Finally, we can also see the negative effects of transfers per capita and the private cost of health care spending. Conclusions. Our study shows that demographic shifts should be considered by public management policies, especially in a developing country context. These may be considered as new challenges to the national public health systems and the necessity of improving the health care management within sub-national levels.